Soil Conservation in the catchment areas of the rivers Ganga & Yumna- A botanical prespective - Gupta, Raj Kumar (Journal of Soil and Water Conservation, 2022)
The conservation of soil and water resources in any catchment is of great importance to the prosperity of the people residing in the locality and have a direct bearing on the population in the lower reaches of the river system, as it greatly fluctuates the flow in the streams and the frequency and severity of the floods.While working on the vegetation of Tehri Garhwal (1960) it has already been suggested by the present author that in order to reduce the silting in the existing reservoirs the natural vegetation, besides factors like land slides, unstable dips and rainfall, plays an important role in the conservation of water and soil and should be kept under constant vigilance. The social and economic conditions of the inhabitants in the catchment areas of these rivers have a direct bearing on the forest vegetation and the land is always under heavy pressure. Since most of the population is of agriculturists, depending directly or indirectly on the forest vegetation, the natural forest wealth is under a constant state of degradation. The result is, that the soils are eroded at a number of places. The scouring process and the load of the silt is increased resulting in the lifting of river beds.